The moderation effect of entrepreneurial resilience on the relationship between financial literacy and sustainable performance - Alshebami, Ali Saleh; Murad, Majid (Frontiers in Psychology, 2022)
The study intends to examine the role of financial literacy in sustainable performance of SME’s in Saudi Arabia, with the moderating effect of entrepreneurial resilience. The data for this study were gathered from 203 different SME’s sector entrepreneurs in Saudi Arabia using a convenience sampling technique. The hypothesis was tested through Smart-PLS software 3.3.9 version and structural equation modeling technique was used to verify the hypothesis relationships. The findings show that financial literacy has a significant and positive impact on sustainable performance. Moreover, results indicate that entrepreneurial resilience has a significant and positive effect on sustainable performance. Furthermore, the findings show that entrepreneurial resilience moderates the relationship between financial literacy and sustainable performance in Saudi Arabia. Lastly, this research article addressed the discussion and practical implications of the study.